Recurrent Chylous Ascites Leading to Transudative Chylothorax Due to Bi-Ventricular Heart Failure - Tuong Vi Cassandra Do DO; Justin Cozza MD; Shyam Ganti MD; Jayaramakrishna Depa MD (SAGE Publishing, 2021)
Chylothorax is a pleural effusion of >110 mg/dL of triglycerides with a milky appearance with transudative being rare. In this article, we present a case of transudative chylothorax with concurrent chylous ascites that is secondary to congestive heart failure (CHF). A 70-year-old male with CHF with ejection fraction of 10%, coronary artery disease status post coronary artery bypass graft, sleep apnea, chronic kidney disease stage 3, and chronic obstructive pulmonary disease presented with worsening abdominal distention, shortness of breath, and increased lower extremities edema. He denied any cough or fever but had orthopnea and paroxysmal nocturnal dyspnea. He requires monthly paracentesis with drainage of 5 to 9 L each time. On physical examination, he had crackles bilaterally with no wheezes or jugular venous distension. His cardiac examination was unremarkable. He did have abdominal distension with dullness to percussion and a positive fluid wave. There was +2 bilateral pitting edema of lower extremities. He had a diagnostic paracentesis where 9.2 L of cloudy milky fluid was drained and therapeutic thoracentesis where 1.1 L of milky fluid was drained. Pleural fluid for triglycerides was 280. His peritoneal fluid had triglycerides of 671 confirming chylous ascites. CHF can lead to chylous ascites due to the increased lymph production in the abdomen, which flows to the thoracic duct. Due to the stiffness at the lymphatic junction, there is high pressure for less flow. The diaphragm plays a role allowing the chylous ascites to be absorb into the thorax.